The Influence of Parental Factors on Gender Performance of Lower Primary School Children - AJIBADE, Abimbola Omotola (The Gender Truth Journal, 2025)
This study examines the influence of parental factors on gender differences in academic performance among lower primary school children. Guided by a descriptive survey research design, the study examined how Parent involvement in school activities, Parent socioeconomic status, Parent educational background, and Parenting style relate to the performance of lower primary school pupils. A sample of pupils and their parents was selected using multi-stage sampling techniques, while data were collected through structured questionnaires and school records. Descriptive statistics and inferential tests were employed to analyse the relationships between variables. Findings from the results show that parent involvement in school activities is the main factor that influences the academic performance of lower primary school pupils. The study concludes that Parental involvement positively influences pupils’ academic performance by equipping parents with the skills to support learning at home. It recommends targeted parental sensitisation on the importance of educational support for children, and school-home collaboration strategies to narrow early gender achievement gaps.